Ensino de História e Religiosidade Afro-brasileira em Codó/MA: uma proposta didática a partir do gênero biográfico - OLIVEIRA, Romário Chaves (2024)
This work aims to build a paradidactic book with the life trajectory of the mother of Saint Nilza Viana in Terecô to be used in elementary schools (initial years) in the municipality of Codó/MA. To support the construction of this educational product, concepts and themes such as culture, identity and plurality were operationalized, in the light of Stuart Hall (2002); teaching knowledge (Tardif, 2014), historical awareness (Rüsen, 2015); history of History Teaching (Bittencourt, 2009) and, last but not least, the history of Afro-Brazilian religiosities and their presence/absence in the History classroom, in dialogue with Coelho (2016) and Carvalho (2009) . To carry out this study, we opted for a descriptive qualitative research approach. Therefore, we will use interviews in order to gather information about how teachers are working with Law 11,645/08 in the classroom and how they cover Terecô, since it is a religion of great expression in the municipality of Codó. So, when carrying out these interviews, it is intended that cultural references are being valued in the teaching practices of the History subject. This study presents as a research problem the following question: what are the spaces and non-spaces of the Afro-religious in the teaching practices of History teachers, since the school environment is a suitable place to deconstruct the religious prejudice established in the city and promote possible dialogues that build and strengthen new identities.